Plasmodium curtails autoimmune nephritis via lasting bone marrow alterations, independent of hemozoin accumulation - Amo, Laura; Kole, Hemanta K.; Scott, Bethany; Qi, Chen-Feng; Krymskaya, Ludmila; Wang, Hongsheng; Miller, Louis H.; Janse, Chris J.; Bolland, Silvia (Frontiers in Immunology, 2023)
The host response against infection with Plasmodium commonly raises self-reactivity as a side effect, and antibody deposition in kidney has been cited as a possible cause of kidney injury during severe malaria. In contrast, animal models show that infection with the parasite confers long-term protection from lethal lupus nephritis initiated by autoantibody deposition in kidney.We have limited knowledge of the factors that make parasite infection more likely to induce kidney damage in humans, or the mechanisms underlying protection from autoimmune nephritis in animal models. Our experiments with the autoimmune-prone FcγR2B[KO] mice have shown that a prior infection with P. yoelii 17XNL protects from end-stage nephritis for a year, even when overall autoreactivity and systemic inflammation are maintained at high levels. In this report we evaluate post-infection alterations, such as hemozoin accumulation and compensatory changes in immune cells, and their potential role in the kidney-specific protective effect by Plasmodium. We ruled out the role of pigment accumulation with the use of a hemozoinrestricted P. berghei ANKA parasite, which induced a self-resolved infection that protected from autoimmune nephritis with the same mechanism as parasitic infections that accumulated normal levels of hemozoin. In contrast, adoptive transfer experiments revealed that bone marrow cells were altered by the infection and could transmit the kidney protective effect to a new host. While changes in the frequency of bone marrow cell populations after infection were variable and unique to a particular parasite strain, we detected a sustained bias in cytokine/chemokine expression that suggested lower fibrotic potential and higher Th1 bias likely affecting multiple cell populations. Sustained changes in bone marrow cell activation profile could have repercussions in immune responses long after the infection was cleared.